If f(x) = 7-2x and g(x) = x+3 . A. What is g^-1 (x) ? B. What is f(g^-1(5)) ?
By signing up, you agree to our Terms of Service and Privacy Policy
A. The inverse function ( g^{-1}(x) ) of ( g(x) = x + 3 ) can be found by interchanging ( x ) and ( y ) in the equation ( y = x + 3 ) and then solving for ( y ). ( y = x + 3 ) Interchanging ( x ) and ( y ): ( x = y + 3 ) Solving for ( y ): ( y = x - 3 ) Therefore, ( g^{-1}(x) = x - 3 ).
B. To find ( f(g^{-1}(5)) ), we substitute ( g^{-1}(5) ) into ( f(x) = 7 - 2x ). ( f(g^{-1}(5)) = 7 - 2 \times (g^{-1}(5)) ) Since ( g^{-1}(5) = 5 - 3 = 2 ), ( f(g^{-1}(5)) = 7 - 2 \times 2 = 7 - 4 = 3 ). Therefore, ( f(g^{-1}(5)) = 3 ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you find the inverse of # y=2x-1#?
- How do you find the asymptotes for #f(x) =(x^3-1)/(x^2-6)#?
- How do you determine if #f(x)=5x# is an even or odd function?
- How do you find the asymptotes for #(2x-4)/(x^2-4)#?
- How do you find the oblique (or slant) asymptote for#( 2x^3 + x^2) / (2x^2 - 3x + 3)#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7